National program for family planning and primary health care Pakistan: a SWOT analysis - Wazir, Mohammad Salim (BioMed Central, 2013)
BACKGROUND: The National Program for Family Planning and Primary Healthcare was launched in 1994. It is one of the largest community based programs in the world, providing primary healthcare services to about 80 million people, most of which is rural poor. The program has been instrumental in improving health related indicators of maternal and child health in the last two decades. METHODS: SWOT analysis was used by making recourse to the structure and dynamics of the program as well as searching the literature. SWOT ANALYSIS: Strengths of the program include: comprehensive design of planning, implementation and supervision mechanisms aided by an MIS, selection and recruitments processes and evidence created through improving health impact indicators. Weaknesses identified are slow progress, poor integration of the program with health services at local levels including MIS, and de-motivational factors such as job insecurity and non-payment of salaries in time. Opportunities include further widening the coverage of services, its potential contribution to health system research, and its use in areas other than health like women empowerment and poverty alleviation. Threats the program may face are: political interference, lack of funds, social threats and implications for professional malpractices. CONCLUSION: Strengthening of the program will necessitate a strong political commitment, sustained funding and a just remuneration to this bare foot doctor of Pakistan, the Lady Health Worker.